Catalytic / heat storage integrated composite material as well as preparation method and application thereof

By introducing catalytic/heat storage integrated composite materials into the photocatalytic material, using the combination of phase-change microcapsules and MOFs shells, the efficiency and stability of the photocatalytic material under temperature changes are solved, and the efficiency and high efficiency of CO2 are achieved Select Conversion.

CN119456050APending Publication Date: 2025-02-18SHUNDE INNOVATION SCHOOL UNIVERSITY OF SCIENCE & TECHNOLOGY BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411698698.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The catalytic efficiency of existing photocatalytic materials for CO2 conversion is greatly affected by temperature changes, resulting in product selectivity, catalyst activity changes, and may lead to catalyst deactivation and decomposition.

Method used

Using catalytic/heat storage integrated composite material, the MOFs shell layer is grown on the surface of the phase-change microcapsules and wrapped in a titanium dioxide spherical shell to achieve partition assembly and functional integration of the photothermal conversion zone, heat storage zone and catalytic zone.

Benefits of technology

The heat storage and temperature control functions are introduced through hierarchical construction methods, the temperature of the catalytic system is adjusted, the efficient and high selection conversion efficiency of CO2 is improved, and the stability of the catalyst is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456050A_ABST
    Figure CN119456050A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of advanced nano composite materials, and discloses a catalysis / heat storage integrated composite material as well as a preparation method and application thereof. The composite material comprises a phase change microcapsule and an MOFs shell layer coating the surface of the phase change microcapsule, wherein the phase change microcapsule takes a phase change material as a core and takes titanium dioxide as a shell. Dropwise adding a solution containing the organic ligand into a solution containing the phase change microcapsule and the MOFs metal precursor, and carrying out a first reaction to obtain the composite material. According to the invention, heat storage and temperature control functions of PCM are introduced into the high-performance TiO2-coated MOFs photocatalytic material by means of hierarchical construction, and efficient conversion of CO2 by a catalytic system is promoted to the maximum extent by using the adjustment effect of the phase change microcapsules on the temperature of the catalytic system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of advanced nanocomposite material preparation, and in particular to a catalytic / heat storage integrated composite material and a preparation method and application thereof. Background Art

[0002] In the past few decades, global carbon dioxide emissions have been on the rise, and excessive CO2 emissions have caused a series of problems such as greenhouse effect, environmental pollution, and sea level rise. Using solar energy to convert CO2 into valuable chemicals or fuels can both reduce the greenhouse effect and alleviate the pressure of energy shortage, so it is very attractive.

[0003] Photocatalytic reduction is a method for converting CO2 into chemicals or fuels with high added value. Its power source can come from sunlight or other artificial light. It has the advantages of low cost and no pollution. It is considered to be one of the most important ways to achieve high-value conversion of CO2. However, due to the thermodynamic stability and kinetic inertness of CO2 (the bond energy of C=O is -750kJ / mol), it is usually necessary to use efficient catalytic materials to reduce the reaction barrier and thus improve the reaction efficiency. However, the catalytic efficiency of the photocatalytic materials currently developed for CO2 conversion is usually greatly affected by the temperature change of the illumination system. Different temperatures will affect the product selectivity and catalyst activity of the catalyst. Excessive temperature may even cause the catalyst to deactivate and decompose.

[0004] Therefore, to further improve the efficiency of using solar energy to convert CO2, two key issues need to be addressed: 1) Developing highly efficient and stable photocatalytic materials; 2) Constructing a temperature-controllable catalytic system to maintain the catalyst in a reasonable temperature range. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a catalytic / heat storage integrated composite material and a preparation method and application thereof.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a catalytic / heat storage integrated composite material, wherein the composite material comprises a phase change microcapsule and a MOFs shell layer coated on the surface of the phase change microcapsule;

[0007] The phase change microcapsule has a phase change material as a core and titanium dioxide as a shell.

[0008] The second aspect of the present invention provides a method for preparing the composite material described in the first aspect, wherein the method comprises: dropping a solution containing an organic ligand into a solution containing phase change microcapsules and MOFs metal precursors, and performing a first reaction to obtain the composite material.

[0009] The present invention first prepares solid spheres of phase change material wrapped in titanium dioxide with a core-shell structure, and then in situ grows a layer of MOFs material with catalytic effect on the surface of the phase change microcapsule to prepare PCM@TiO2@MOFs functional material, thereby realizing the partitioned assembly and functional integration of the photothermal conversion zone, the heat storage zone and the catalytic zone.

[0010] The third aspect of the present invention provides a catalytic / heat storage integrated composite material obtained according to the preparation method described in the second aspect.

[0011] The fourth aspect of the present invention provides use of the integrated catalytic / heat storage composite material described in the first aspect or the third aspect in photocatalytic reduction of carbon dioxide.

[0012] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0013] (1) The present invention introduces the heat storage and temperature control functions of PCM into high-performance TiO2@MOFs photocatalytic materials by means of hierarchical construction, and utilizes the temperature regulation effect of phase change microcapsules on the catalytic system to maximize the promotion of the catalytic system's efficient and highly selective conversion of CO2.

[0014] (2) The preparation process of the catalytic / heat storage integrated composite material provided by the present invention is simple, the reaction conditions are mild, and the cycle is short. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a scanning electron microscope photograph of n-docosane@TiO2 obtained in Example 1 of the present invention.

[0016] Figure 2 This is a scanning electron microscope photograph of n-docosane@TiO2@ZIF-8 obtained in Example 1 of the present invention.

[0017] Figure 3 This is the DSC graph of n-docosane@TiO2@ZIF-8 obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The first aspect of the present invention provides a catalytic / heat storage integrated composite material, wherein the composite material comprises a phase change microcapsule and a MOFs shell layer coated on the surface of the phase change microcapsule;

[0020] The phase change microcapsule has a phase change material as a core and titanium dioxide as a shell.

[0021] The present invention provides a new type of PCM@TiO2@MOFs functional material by organically assembling phase change materials (PCM) and metal organic frameworks (MOFs) and introducing a TiO2 encapsulation shell layer, and performs partitioned assembly and functional integration of photothermal conversion zones, heat storage zones and catalytic zones.

[0022] MOFs absorb visible light to generate photogenerated electrons and holes, and TiO2 absorbs ultraviolet light to generate photogenerated electrons and holes. The heterojunction formed by TiO2 and MOFs can promote the transfer of photogenerated electrons from the conduction band of MOFs to the conduction band of TiO2. The highly active TiO2 efficiently catalyzes the conversion of CO2 enriched on the surface of MOFs. PCM can effectively store the heat energy generated by light and reduce heat loss. At the same time, it uses its own phase change characteristics and heat collection effect to ensure the constancy of the temperature of the catalytic material and the uniformity of heating, thereby maximizing the promotion of efficient conversion of CO2.

[0023] In some embodiments of the present invention, the phase change material is selected from at least one of dodecane, tetradecane, hexadecane, octadecane, eicosane and docosane, preferably n-docosane and / or n-eicosane. The present invention can select a suitable phase change material according to the reaction temperature of the system by selecting the type of phase change material, and reasonably regulate the system temperature.

[0024] In some embodiments of the present invention, the material of the MOFs shell is selected from at least one of ZIF-8, ZIF-67, CuBTC and MIL-100, preferably ZIF-8 and / or ZIF-67. The present invention regulates the product of photocatalytic reduction of CO2, the optimal operating temperature of the system and the wavelength range by selecting the type of MOFs material.

[0025] In some embodiments of the present invention, the thickness of the titanium dioxide is 100-300 nm, preferably 200 nm. In the present invention, if the thickness of the titanium dioxide is too large, the heat transfer efficiency will be affected, and if the thickness is too small, the PCM is prone to leakage and the photocatalytic active sites are reduced.

[0026] In some embodiments of the present invention, the thickness of the MOFs shell is 10-200 nm, preferably 100 nm. In the present invention, if the thickness of the MOFs shell is too large, it will affect the transport of CO2 and products, and the stability of the system will be reduced; if the thickness of the MOFs shell is too small, there will be few active sites for catalytic reaction, low gas adsorption, and affect the catalytic performance of the system.

[0027] In some embodiments of the present invention, the average particle size of the core is 1-10 μm, preferably 5 μm. In the present invention, if the average particle size of the core is too large, the heat transfer capacity and stability will be poor; if the average particle size of the core is too small, the heat storage capacity will be small and the temperature control performance will be poor.

[0028] The second aspect of the present invention provides a method for preparing the composite material described in the first aspect, wherein the method comprises: dropping a solution containing an organic ligand into a solution containing phase change microcapsules and MOFs metal precursors, and performing a first reaction to obtain the composite material.

[0029] The present invention first synthesizes phase-change microcapsules of phase-change materials wrapped in titanium dioxide spherical shells. The phase-change materials play a role in phase-change temperature control. During the phase change process, they not only absorb or release heat, but also may produce light, electricity and other effects. These effects can interact with the photocatalytic process to form photothermal synergistic catalysis. It is wrapped in a titanium dioxide spherical shell to effectively prevent the leakage of the phase-change material, and titanium dioxide itself has the ability to catalyze the conversion of CO2. Then, a layer of MOFs shell with strong light absorption ability is wrapped outside the titanium dioxide spherical shell to obtain a PCM@TiO2@MOFs catalytic / heat storage integrated composite material.

[0030] In some embodiments of the present invention, the organic ligand is selected from at least one of 2-methylimidazole, terephthalic acid, phthalic acid, trimesic acid, pyromellitic acid and mellitic acid, preferably 2-methylimidazole.

[0031] In some embodiments of the present invention, the MOFs metal precursor is selected from at least one of zinc nitrate, copper nitrate, copper sulfate, nickel nitrate and cobalt nitrate, preferably zinc nitrate and / or cobalt nitrate.

[0032] In some embodiments of the present invention, the molar ratio of the organic ligand to the metal ion in the MOFs metal precursor is 2-10:1, preferably 6:1.

[0033] In some embodiments of the present invention, the time of the first reaction is 2-8 hours, preferably 4 hours.

[0034] In some embodiments of the present invention, the product of the first reaction is filtered, washed, and then first dried to obtain the composite material.

[0035] In some embodiments of the present invention, the first drying conditions include: room temperature; time is 12-48 hours, preferably 24 hours.

[0036] In some embodiments of the present invention, the method for preparing the phase change microcapsules comprises:

[0037] (1) in the presence of an organic solvent, allowing the phase change material, the polyoxypropylene-polyoxyethylene copolymer solution and the titanium source to undergo a second reaction to obtain a second reaction product;

[0038] (2) Adding the formamide aqueous solution dropwise to the second reaction product to carry out a third reaction to obtain phase change microcapsules.

[0039] In some embodiments of the present invention, in step (1), the organic solvent is formamide.

[0040] In some embodiments of the present invention, the titanium source is tetrabutyl titanate.

[0041] In some embodiments of the present invention, the mass ratio of the phase change material, the polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer and the titanium source is 1-10:0.5-2:2-6, preferably 4:0.84:4.

[0042] In some embodiments of the present invention, the conditions of the second reaction include: temperature of 40-60°C, preferably 50°C; stirring rate of 300-600rpm, preferably 450rpm; time of 4-8h, preferably 5h.

[0043] In some embodiments of the present invention, in step (2), the volume ratio of formamide to water in the formamide aqueous solution is 30-50:1-10, preferably 20:1.

[0044] In some embodiments of the present invention, the conditions of the third reaction include: temperature of 40-60°C, preferably 50°C; stirring rate of 300-600rpm, preferably 450rpm; time of 4-8h, preferably 5h.

[0045] In some embodiments of the present invention, the product of the third reaction is filtered, washed, and then subjected to a second drying to obtain phase change microcapsules.

[0046] In some embodiments of the present invention, the second drying conditions include: room temperature; time is 2-30 hours, preferably 24 hours.

[0047] According to a particularly preferred embodiment of the present invention, a method for preparing a catalytic / heat storage integrated composite material comprises the following steps:

[0048] (1) First, 1-10 g of phase change material, 0.5-2 g of polyoxypropylene polyoxyethylene copolymer solution (PEO-PPO-PEO), and 2-6 mL of tetrabutyl titanate (TBT) are mixed and dissolved in 40-200 mL of formamide, and stirred evenly;

[0049] (2) reacting at 40-60°C with a stirring rate of 300-600 rpm for 4-8 hours;

[0050] (3) Mix 30-50 mL of formamide with 1-10 mL of deionized water, and slowly add dropwise to the reaction product of step (2);

[0051] (4) Keep the heating temperature and stirring rate unchanged and continue the reaction for 4-8 hours;

[0052] (5) filtering the reaction product of step (4) and washing it with deionized water several times to obtain a white precipitate, and drying it at room temperature for 2-30 hours; the white precipitate is a phase change microcapsule of a phase change material encapsulated by a titanium dioxide spherical shell;

[0053] (6) The white precipitate obtained above is evenly mixed in the solution containing the MOFs metal precursor and stirred evenly for 10-150 minutes;

[0054] (7) Take the same volume of solution containing organic ligand and stir evenly for 10-150 min until the ligand is completely dissolved in the solution;

[0055] (8) Add the solution obtained in step (7) dropwise to the system of step (6) and stir for 2-8 hours;

[0056] (9) The reaction product of step (8) was filtered and rinsed with deionized water several times to obtain a precipitate, which was then dried at room temperature for 12-48 h to obtain a PCM@TiO2@MOFs composite material.

[0057] The third aspect of the present invention provides a catalytic / heat storage integrated composite material obtained according to the preparation method described in the second aspect.

[0058] The fourth aspect of the present invention provides use of the integrated catalytic / heat storage composite material described in the first aspect or the third aspect in photocatalytic reduction of carbon dioxide.

[0059] The present invention will be described in detail below through examples.

[0060] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0061] In the following examples, the polyoxypropylene-polyoxyethylene copolymer solution was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 106392-12-5, item No. T832531-25g, batch No. C15554203.

[0062] Example 1

[0063] This example is used to illustrate the preparation of a catalytic / heat storage integrated composite material.

[0064] (1) First, 4 g of n-docosane, 0.84 g of polyoxypropylene-polyoxyethylene copolymer solution (PEO-PPO-PEO), and 4 mL of tetrabutyl titanate (TBT) were mixed and dissolved in 80 mL of formamide in a flask and stirred evenly;

[0065] (2) React at 50°C with a stirring rate of 450 rpm for 5 h;

[0066] (3) Mix 40 mL of formamide with 2 mL of deionized water and slowly add dropwise to the flask;

[0067] (4) Keep the heating temperature and stirring rate unchanged and continue the reaction for 5 hours;

[0068] (5) filtering the reaction product in step (4) and washing it with deionized water several times to obtain a white precipitate, and drying it at room temperature for 24 hours; the white precipitate is a phase change microcapsule of n-docosane encapsulated by a titanium dioxide spherical shell;

[0069] (6) The white precipitate obtained above was uniformly mixed in a methanol solution containing 2 mmol Zn(NO3)2·6H2O and stirred uniformly for 15 min;

[0070] (7) Take an equal volume of methanol solution containing 0.012 mol of 2-methylimidazole (2-MIm) powder and stir evenly for 15 min until the 2-MIm powder is completely dissolved in methanol;

[0071] (8) Add the solution obtained in step (7) dropwise to the system in step (6) and stir to react for 4 hours;

[0072] (9) The reaction product of step (8) was filtered and rinsed with deionized water several times to obtain an off-white precipitate, which was dried at room temperature for 24 h; the off-white precipitate was the n-docosane@TiO2@ZIF-8 composite material.

[0073] In the composite material, the thickness of titanium dioxide is 200 nm, the thickness of the MOFs shell is 100 nm, and the average particle size of the core is 5 μm.

[0074] Example 2

[0075] This example is used to illustrate the preparation of a catalytic / heat storage integrated composite material.

[0076] (1) First, 4 g of n-eicosane, 0.84 g of polyoxypropylene-polyoxyethylene copolymer solution (PEO-PPO-PEO), and 4 mL of tetrabutyl titanate (TBT) were mixed and dissolved in 80 mL of formamide in a flask and stirred evenly;

[0077] (2) React at 50°C with a stirring rate of 450 rpm for 5 h;

[0078] (3) Mix 40 mL of formamide and 2 mL of deionized water and slowly add them dropwise to the flask;

[0079] (4) Keep the heating temperature and stirring rate unchanged and continue the reaction for 5 hours;

[0080] (5) filtering the reaction product in step (4) and washing it with deionized water several times to obtain a white precipitate, and drying it at room temperature for 24 hours; the white precipitate is a phase change microcapsule of n-eicosane encapsulated by a titanium dioxide spherical shell;

[0081] (6) The white precipitate obtained above was evenly mixed in a methanol solution containing 2 mmol Zn(NO3)2·6H2O and stirred evenly for 15 min;

[0082] (7) Take an equal volume of methanol solution containing 0.012 mol of 2-methylimidazole (2-MIm) powder and stir evenly for 15 min until the 2-MIm powder is completely dissolved in methanol;

[0083] (8) Add the solution obtained in step (7) dropwise to the system in step (6) and stir to react for 4 hours;

[0084] (9) The reaction product of step (8) was filtered and rinsed with deionized water several times to obtain an off-white precipitate, which was dried at room temperature for 24 h; the off-white precipitate was the n-eicosane@TiO2@ZIF-8 composite material.

[0085] In the composite material, the thickness of titanium dioxide is 200 nm, the thickness of the MOFs shell is 100 nm, and the average particle size of the core is 5 μm.

[0086] Example 3

[0087] This example is used to illustrate the preparation of a catalytic / heat storage integrated composite material.

[0088] (1) First, 4 g of n-docosane, 0.84 g of polyoxypropylene-polyoxyethylene copolymer solution (PEO-PPO-PEO), and 4 mL of tetrabutyl titanate (TBT) were mixed and dissolved in 80 mL of formamide in a flask and stirred evenly;

[0089] (2) heating at 50°C and stirring at 450 rpm for 5 h;

[0090] (3) Mix 40 mL of formamide with 2 mL of deionized water and slowly add dropwise to the flask;

[0091] (4) Keep the heating temperature and stirring rate unchanged and continue the reaction for 5 hours;

[0092] (5) filtering the reaction product in step (4) and washing it with deionized water several times to obtain a white precipitate, and drying it at room temperature for 24 hours; the white precipitate is a phase change microcapsule of n-docosane encapsulated by a titanium dioxide spherical shell;

[0093] (6) The white precipitate obtained above was evenly mixed in a methanol solution containing 2 mmol Co(NO3)2·6H2O and stirred evenly for 15 min;

[0094] (7) Take an equal volume of methanol solution containing 0.012 mol of 2-methylimidazole (2-MIm) powder and stir evenly for 15 min until the 2-MIm powder is completely dissolved in methanol;

[0095] (8) Add the solution obtained in step (7) dropwise to the system of step (6) and stir to react for 4 hours;

[0096] (9) The reaction product of step (8) was filtered and rinsed with deionized water several times to obtain a blue-purple precipitate, which was dried at room temperature for 24 h; the blue-purple precipitate was the n-docosane@TiO2@ZIF-67 composite material.

[0097] In the composite material, the thickness of titanium dioxide is 200 nm, the thickness of the MOFs shell is 100 nm, and the average particle size of the core is 5 μm.

[0098] Example 4

[0099] This example is used to illustrate the preparation of a catalytic / heat storage integrated composite material.

[0100] (1) First, 4 g of n-docosane, 0.84 g of polyoxypropylene-polyoxyethylene copolymer solution (PEO-PPO-PEO), and 4 mL of tetrabutyl titanate (TBT) were mixed and dissolved in 80 mL of formamide in a flask and stirred evenly;

[0101] (2) React at 50°C with a stirring rate of 450 rpm for 5 h;

[0102] (3) Mix 40 mL of formamide and 4 mL of deionized water and slowly add them dropwise to the flask;

[0103] (4) Keep the heating temperature and stirring rate unchanged and continue the reaction for 5 hours;

[0104] (5) filtering the reaction product in step (4) and washing it with deionized water several times to obtain a white precipitate, and drying it at room temperature for 24 hours; the white precipitate is a phase change microcapsule of n-docosane encapsulated by a titanium dioxide spherical shell;

[0105] (6) The white precipitate obtained above was evenly mixed in a methanol solution containing 2 mmol Zn(NO3)2·6H2O and stirred evenly for 15 min;

[0106] (7) Take an equal volume of methanol solution containing 0.012 mol of 2-methylimidazole (2-MIm) powder and stir evenly for 15 min until the 2-MIm powder is completely dissolved in methanol;

[0107] (8) Add the solution obtained in step (7) dropwise to the system in step (6) and stir to react for 4 hours;

[0108] (9) The reaction product of step (8) was filtered and rinsed with deionized water several times to obtain an off-white precipitate, which was dried at room temperature for 24 h; the off-white precipitate was the n-docosane@TiO2@ZIF-8 composite material.

[0109] In the composite material, the thickness of titanium dioxide is 240 nm, the thickness of the MOFs shell is 100 nm, and the average particle size of the core is 5 μm.

[0110] Example 5

[0111] This example is used to illustrate the preparation of a catalytic / heat storage integrated composite material.

[0112] (1) First, 4 g of n-docosane, 0.84 g of polyoxypropylene-polyoxyethylene copolymer solution (PEO-PPO-PEO), and 4 mL of tetrabutyl titanate (TBT) were mixed and dissolved in 80 mL of formamide in a flask and stirred evenly;

[0113] (2) React at 50°C with a stirring rate of 450 rpm for 5 h;

[0114] (3) Mix 40 mL of formamide with 2 mL of deionized water and slowly add dropwise to the flask;

[0115] (4) Keep the heating temperature and stirring rate unchanged and continue the reaction for 5 hours;

[0116] (5) filtering the reaction product in step (4) and washing it with deionized water several times to obtain a white precipitate, and drying it at room temperature for 24 hours; the white precipitate is a phase change microcapsule of n-docosane encapsulated by a titanium dioxide spherical shell;

[0117] (6) The white precipitate obtained above was uniformly mixed in a methanol solution containing 1 mmol Zn(NO3)2·6H2O and stirred uniformly for 15 min;

[0118] (7) Take an equal volume of methanol solution containing 0.006 mol of 2-methylimidazole (2-MIm) powder and stir evenly for 15 min until the 2-MIm powder is completely dissolved in methanol;

[0119] (8) Add the solution obtained in step (7) dropwise to the system in step (6) and stir to react for 4 hours;

[0120] (9) The reaction product of step (8) was filtered and rinsed with deionized water several times to obtain an off-white precipitate, which was dried at room temperature for 24 h; the off-white precipitate was the n-docosane@TiO2@ZIF-8 composite material.

[0121] In the composite material, the thickness of titanium dioxide is 200 nm, the thickness of the MOFs shell is 60 nm, and the average particle size of the core is 5 μm.

[0122] Example 6

[0123] This example is used to illustrate the preparation of a catalytic / heat storage integrated composite material.

[0124] (1) First, 4 g of n-docosane, 0.84 g of polyoxypropylene-polyoxyethylene copolymer solution (PEO-PPO-PEO), and 4 mL of tetrabutyl titanate (TBT) were mixed and dissolved in 80 mL of formamide in a flask and stirred evenly;

[0125] (2) React at 50°C with a stirring rate of 450 rpm for 5 h;

[0126] (3) Mix 40 mL of formamide with 2 mL of deionized water and slowly add dropwise to the flask;

[0127] (4) Keep the heating temperature and stirring rate unchanged and continue the reaction for 5 hours;

[0128] (5) filtering the reaction product in step (4) and washing it with deionized water several times to obtain a white precipitate, and drying it at room temperature for 24 hours; the white precipitate is a phase change microcapsule of n-docosane encapsulated by a titanium dioxide spherical shell;

[0129] (6) The white precipitate obtained above was uniformly mixed in a methanol solution containing 4 mmol Zn(NO3)2·6H2O and stirred uniformly for 15 min;

[0130] (7) Take an equal volume of methanol solution containing 0.024 mol of 2-methylimidazole (2-MIm) powder and stir evenly for 15 min until the 2-MIm powder is completely dissolved in methanol;

[0131] (8) Add the solution obtained in step (7) dropwise to the system in step (6) and stir to react for 4 hours;

[0132] (9) The reaction product of step (8) was filtered and rinsed with deionized water several times to obtain an off-white precipitate, which was dried at room temperature for 24 h; the off-white precipitate was the n-docosane@TiO2@ZIF-8 composite material.

[0133] In the composite material, the thickness of titanium dioxide is 200 nm, the thickness of the MOFs shell is 120 nm, and the average particle size of the core is 5 μm.

[0134] Comparative Example 1

[0135] The composite material was prepared according to the method of Example 1, except that n-docosane was not added in step (1).

[0136] Comparative Example 2

[0137] The composite material was prepared according to the method of Example 2, except that n-eicosane was not added in step (1).

[0138] Comparative Example 3

[0139] The composite material was prepared according to the method of Example 3, except that n-docosane was not added in step (1).

[0140] Test Example 1

[0141] The CO2 reduction performance test was carried out using a gas-solid phase photocatalytic CO2 reduction test system.

[0142] The reaction device was the Labsolar-6A photocatalytic test system of Perfekt Technology Co., Ltd. 5 mg of the sample was dispersed in an ethanol solution and then dropped onto the glass fiber membrane and vacuum dried overnight for use. The glass fiber membrane loaded with the sample was placed on a glass tray, which was placed inside a glass reactor. 2 mL of deionized water was injected into the bottom of the reactor to provide water vapor for the reaction. The light source was a 300 W xenon lamp (Perfekt, PLS-SXE300D) equipped with an AM 1.5G filter to simulate sunlight. After the reaction device was assembled, it was evacuated and passed through high-purity CO2 gas and then purified twice to exhaust the air in the reaction device. The reactor pressure was maintained at 80 kPa, and the reactor temperature was maintained at 5 °C by water cooling. After waiting for 1 hour for CO2 gas to fully contact with the sample, the light was turned on for testing. A Shimadzu gas chromatograph (2014a) equipped with an FID detector and a TCD detector was used to detect possible gas products.

[0143] The results are shown in Table 1.

[0144] Table 1

[0145] serial number CO production rate, μmol / g / h Example 1 100 Example 2 95 Example 3 120 Example 4 80 Example 5 85 Example 6 90 Comparative Example 1 75 Comparative Example 2 70 Comparative Example 3 80

[0146] It can be seen from the results in Table 1 that the composite material provided by the present invention has good CO2 reduction performance.

[0147] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalytic / heat storage integrated composite material, characterized in that: The composite material comprises a phase-change microcapsule and a MOFs shell layer coated on the surface of the phase-change microcapsule; The phase change microcapsule has a phase change material as a core and titanium dioxide as a shell.

2. The composite material according to claim 1, wherein The phase change material is selected from at least one of dodecane, tetradecane, hexadecane, octadecane, eicosane and docosane, preferably n-docosane and / or n-eicosane; Preferably, the material of the MOFs shell layer is selected from at least one of ZIF-8, ZIF-67, CuBTC and MIL-100, preferably ZIF-8 and / or ZIF-67.

3. The composite material according to claim 1 or 2, wherein: The thickness of the titanium dioxide is 100-300 nm, preferably 200 nm; Preferably, the thickness of the MOFs shell is 10-200 nm, preferably 100 nm; Preferably, the average particle size of the core is 1-10 μm, preferably 5 μm.

4. A method for preparing a composite material according to any one of claims 1 to 3, characterized in that: The method comprises: dropping a solution containing an organic ligand into a solution containing phase-change microcapsules and MOFs metal precursors, and performing a first reaction to obtain the composite material.

5. The preparation method according to claim 4, wherein The organic ligand is selected from at least one of 2-methylimidazole, terephthalic acid, phthalic acid, trimesic acid, pyromellitic acid and mellitic acid, preferably 2-methylimidazole; Preferably, the MOFs metal precursor is selected from at least one of zinc nitrate, copper nitrate, copper sulfate, nickel nitrate and cobalt nitrate, preferably zinc nitrate and / or cobalt nitrate; Preferably, the molar ratio of the organic ligand to the metal ion in the MOFs metal precursor is 2-10:1, preferably 6:1; Preferably, the first reaction time is 2-8h, preferably 4h; Preferably, the product of the first reaction is filtered, washed, and then first dried to obtain the composite material; Preferably, the first drying conditions include: room temperature; time is 12-48 hours, preferably 24 hours.

6. The preparation method according to claim 4 or 5, wherein: The preparation method of the phase change microcapsule comprises: (1) in the presence of an organic solvent, allowing the phase change material, the polyoxypropylene-polyoxyethylene copolymer solution and the titanium source to undergo a second reaction to obtain a second reaction product; (2) Adding the formamide aqueous solution dropwise to the second reaction product to carry out a third reaction to obtain phase change microcapsules.

7. The preparation method according to any one of claims 4 to 6, wherein In step (1), the organic solvent is formamide; Preferably, the titanium source is tetrabutyl titanate; Preferably, the mass ratio of the phase change material, the polyoxypropylene polyoxyethylene copolymer solution and the titanium source is 1-10:0.5-2:2-6, preferably 4:0.84:4; Preferably, the conditions of the second reaction include: temperature of 40-60°C, preferably 50°C; stirring rate of 300-600rpm, preferably 450rpm; time of 4-8h, preferably 5h.

8. The preparation method according to any one of claims 4 to 7, wherein In step (2), the volume ratio of formamide to water in the formamide aqueous solution is 30-50:1-10, preferably 20:1; Preferably, the conditions of the third reaction include: temperature of 40-60°C, preferably 50°C; stirring rate of 300-600rpm, preferably 450rpm; time of 4-8h, preferably 5h; Preferably, the product of the third reaction is filtered, washed, and then subjected to a second drying to obtain phase change microcapsules; Preferably, the second drying conditions include: room temperature; time of 2-30 hours, preferably 24 hours.

9. The catalytic / heat storage integrated composite material obtained by the preparation method according to any one of claims 4 to 8.

10. Use of the integrated catalytic / heat storage composite material according to any one of claims 1 to 3 and 9 in photocatalytic reduction of carbon dioxide.